Repackaging FDI for inclusive growth: Nullifying effects and policy relevant thresholds of governance - Isaac Kwesi Ofori; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
This study examines whether the remarkable inflow of resources in the form of foreign direct investment (FDI) to SSA contributes to inclusive growth in the region. The study further investigates whether SSA's institutional fabric modulates the effect of FDI on inclusive growth in SSA. To this end, we draw data on 42 SSA countries for the period 1990 - 2020 for the analysis. The evidence, which are based on the GMM estimator shows that: (1) though FDI fosters inclusive growth in SSA, the effect is weak, and (2) the weak inclusive growth inducing-effects of FDI are weakened or nullified completely by SSA' fragile governance quality. Nonetheless, the optimism, which we provide by way of threshold analysis shows that channelling resources into the development of these governance dynamics yield positive net effects from the short-term through to the long-term. Notably, the results show that the short-term to long-term FDI-induced inclusive growth gains of developing frameworks and structures for fighting corruption while addressing fragilities in regulatory quality and government effectiveness are outstanding. A few policy recommendations are discussed in the end.
Keywords: F6; F15; O43; O55; R58; 330; AfCFTA; Africa; Economic Integration; FDI; Governance; Inclusive Growth